Preface - Nowak, Andrzej J. (Computer Assisted Methods in Engineering and Science, 2013)
Papers published in this special issue (and the papers of already published special issue CAMES 2/2013) have been presented during the Numerical Heat Transfer 2012 International Conference (NHT2012).